A carbon nanotube-containing heat sink and a method for manufacturing the same

CN122935241APending Publication Date: 2026-10-16SHENZHEN MINGRUIDA HARDWARE PROD CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611095097.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-22
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

[0004]本发明所要解决的技术问题在于提供一种含碳纳米管的散热片及其制备方法,旨在解决现有散热片容易出现局部热点、散热不均匀的问题

Benefits of technology

[0007]由上述技术方案可知,本公开示例性实施例中至少具备以下优点和积极效果:

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122935241A_ABST
    Figure CN122935241A_ABST
Patent Text Reader

Abstract

This invention proposes a carbon nanotube-containing heat sink and its preparation method. The steps include: roughening the surface of a heat sink substrate, performing degreasing and cleaning, and hydrophilic activation treatment to obtain a heat sink preform. The heat sink substrate includes a base and fins. Carbon nanotubes and a dispersant are added to a dispersion medium to obtain a carbon nanotube dispersion. The heat sink preform is placed in the carbon nanotube dispersion. The base is used as a deposition electrode, and an electric field aligned with the target heat conduction direction is applied to deposit carbon nanotubes onto the base, forming an outward heat-conducting layer. The direction of the electric field is adjusted to deposit carbon nanotubes onto the fins, forming an oriented heat-releasing layer, resulting in a deposition composite. The deposition composite is then subjected to a liquid removal treatment. The outward heat-conducting layer is hot-pressed for densification. The oriented heat-releasing layer is then vacuum-heat-bonded. Finally, an auxiliary fixing liquid is sprayed to obtain the carbon nanotube-containing heat sink. This method directs heat from the base to the fins near the heat source, thereby improving uneven heat distribution.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of carbon nanotube technology, and particularly relates to a heat sink containing carbon nanotubes and its preparation method. Background Technology

[0002] Power devices and chips generate power consumption during conduction, switching, and operation, most of which is ultimately converted into heat. For example, MOSFETs, IGBTs, CPUs, GPUs, and power modules generate significant heat when operating under high current, high frequency switching, or high load conditions. These devices are typically small, resulting in concentrated heat; relying solely on natural heat dissipation is insufficient for timely heat dissipation. The purpose of heat sinks is to increase the surface area exposed to air and, through highly thermally conductive materials, rapidly conduct the heat generated inside the device to the outside, thereby reducing the device's junction temperature.

[0003] However, in the actual operation of power devices, power modules, or highly integrated chips, heat is usually not generated uniformly across the entire device surface. Instead, it tends to concentrate in the chip core area, conductive channel area, switching junction area, or localized high-load areas. In this case, heat first accumulates rapidly in localized areas, forming high temperature peaks. Traditional heat sinks, due to their relatively simple heat conduction paths and lack of targeted design for the internal heat conduction direction of the material, often rely solely on the natural diffusion capacity of the metal substrate to gradually transfer heat from the center to the periphery. During this process, areas near the heat source experience rapid temperature rise and high heat flux density, while areas farther from the heat source dissipate heat more slowly, resulting in uneven temperature distribution across the heat sink and the formation of noticeable hot spots. Once hot spots form, not only will the corresponding area remain in a high-temperature environment for a prolonged period, but significant temperature differences will also occur between different locations within the device, leading to problems such as thermal stress concentration, package interface fatigue, solder joint aging, and material performance drift. Summary of the Invention

[0004] The technical problem to be solved by the present invention is to provide a heat sink containing carbon nanotubes and its preparation method, which aims to solve the problems of local hot spots and uneven heat dissipation that are easy to occur in existing heat sinks.

[0005] According to one aspect of this disclosure, a method for preparing a heat sink containing carbon nanotubes is provided, comprising the following steps: S1. The heat dissipation substrate is subjected to surface roughening treatment, degreasing cleaning and hydrophilic activation treatment to obtain heat dissipation preform, wherein the heat dissipation substrate includes a base and fins. S2. Carbon nanotubes and dispersant are added to a dispersion medium to disperse carbon nanotubes to obtain a carbon nanotube dispersion. The heat dissipation preform is placed in the carbon nanotube dispersion. The base is used as a deposition electrode to apply an electric field consistent with the target heat conduction direction, so that carbon nanotubes are deposited on the base to form an oriented heat conduction layer. The direction of the electric field is adjusted to deposit carbon nanotubes on the fins to form an oriented heat release layer, thus obtaining a deposition composite. S3. The deposited composite is dehydrated, the heat-conducting layer is hot-pressed and densified, the oriented heat-releasing layer is vacuum heat-fixed, and then an auxiliary fixing liquid is sprayed on. After drying, a heat sink containing carbon nanotubes is obtained.

[0006] According to one aspect of this disclosure, a heat sink containing carbon nanotubes is provided, which is manufactured by the method described above for preparing a heat sink containing carbon nanotubes. The heat sink containing carbon nanotubes includes a base, fins, a heat-conducting layer disposed on the base, and an oriented heat-releasing layer disposed on the fins. Both the heat-conducting layer and the oriented heat-releasing layer contain carbon nanotubes. The heat-conducting layer is used to construct a heat conduction path extending along the target heat conduction direction, and the oriented heat-releasing layer is used to construct a heat diffusion and heat release path extending along the surface of the fins.

[0007] As can be seen from the above technical solutions, the exemplary embodiments disclosed herein possess at least the following advantages and positive effects: First, in step S1, the heat dissipation substrate undergoes surface roughening treatment, followed by degreasing, cleaning, and hydrophilic activation treatment to obtain a heat dissipation preform. Since the heat dissipation substrate includes a base and fins, this means that both the base and fins undergo uniform surface pretreatment before subsequent deposition. Surface roughening helps to change the surface state of the heat dissipation substrate, degreasing removes surface impurities, and hydrophilic activation treatment makes the heat dissipation preform more suitable for contact with the carbon nanotube dispersion.

[0008] Secondly, in step S2, carbon nanotubes and a dispersant are added to a dispersion medium for dispersion to obtain a carbon nanotube dispersion. This technical feature allows carbon nanotubes to participate in subsequent deposition in a dispersed state, thus providing a basis for their directional deposition under the action of an electric field. Subsequently, the heat dissipation preform is placed in the carbon nanotube dispersion, and the base is used as a deposition electrode to apply an electric field consistent with the target heat conduction direction, causing the carbon nanotubes to be deposited on the base and forming an outward heat conduction layer. This outward heat conduction layer is formed directly around the target heat conduction direction. Heat at the base no longer mainly relies on the relatively dispersed diffusion of the substrate itself, but can be transferred more specifically along the direction corresponding to the outward heat conduction layer, reducing the possibility of heat stagnation near local heat sources.

[0009] Furthermore, after the heat-conducting layer is formed on the base, carbon nanotubes are deposited on the fins by adjusting the direction of the electric field, forming an oriented heat-releasing layer. Since the fins are the part of the heat dissipation substrate responsible for outward heat release, this step does not involve forming the same structure across the entire area. Instead, by adjusting the direction of the electric field, the carbon nanotubes form an oriented heat-releasing layer at the fins that is compatible with the heat-releasing function. In this way, after heat is conducted away through the heat-conducting layer on the base, it can continue to diffuse along the corresponding oriented structure at the fin location, entering the fin area more suitable for heat release, rather than accumulating at the transition between the base and the fins or being confined to a localized area.

[0010] Finally, in step S3, the thermally conductive layer is subjected to hot-pressing densification, and the oriented heat-releasing layer is subjected to vacuum thermal consolidation. This demonstrates that the carbon nanotube layers on the base and fins are further stabilized and consolidated after formation, thereby ensuring that the aforementioned thermally conductive oriented structure formed on the base and the heat-releasing oriented structure formed on the fins are retained and stably attached to the surface of the heat dissipation substrate. Combined with spraying an auxiliary fixing liquid and drying, the entire deposition composite ultimately forms a relatively stable carbon nanotube-containing heat sink structure. This allows heat to be transferred and diffused more orderly from the local heat source area to the fin area, thereby improving the shortcomings of existing heat sinks, such as heat concentration, excessive local temperature rise, and insufficient overall area utilization. Attached Figure Description

[0011] Figure 1 This is a schematic diagram of the structure of a heat sink containing carbon nanotubes in one embodiment of the present invention; Figure 2 This is a schematic flowchart of a method for preparing a heat sink containing carbon nanotubes according to an embodiment of the present invention. Figure 3 This is a front view of a heat sink containing carbon nanotubes according to an embodiment of the present invention; Figure 4 This is a side view of a heat sink containing carbon nanotubes according to an embodiment of the present invention; Figure 5 This is a rear view of a heat sink containing carbon nanotubes according to an embodiment of the present invention.

[0012] 100. Fins; 200. Base. Detailed Implementation

[0013] To make the objectives, technical solutions, and advantages of this invention clearer, the invention will be further described in detail below with reference to the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are merely illustrative and not intended to limit the invention.

[0014] Please refer to Figure 2 This invention proposes a method for preparing a heat sink containing carbon nanotubes, the steps of which include: S1. The heat dissipation substrate undergoes surface roughening treatment, degreasing cleaning, and hydrophilic activation treatment to obtain a heat dissipation prefabricated component. The heat dissipation substrate includes a base 200 and fins 100. The heat dissipation substrate includes one of aluminum alloy heat sinks, copper alloy heat sinks, or copper-aluminum composite heat sinks.

[0015] Step S1 includes: S1.1 The base 200 of the heat dissipation substrate is roughened by a directional sandblasting device. The sandblasting medium is 100-180 mesh alumina sand or silicon carbide sand, the spraying pressure is 0.35-0.65MPa, the angle between the spray gun and the surface of the base 200 is controlled at 30-60°, the scanning speed is 30-120mm / s, and the processing time is 20-90s.

[0016] A directional sandblasting device is used to roughen the surface of the base 200, forming a fine uneven structure distributed along the blasting scanning direction. This increases the actual contact area of ​​the base 200 surface and provides more interlocking sites for subsequent carbon nanotube deposition in the base 200 region. The sandblasting medium is selected from 100-180 mesh alumina sand or silicon carbide sand. These two materials have high hardness and can effectively remove the weak oxide layer and processing residues from the surface of the base 200, forming a noticeable but not too deep rough texture on the metal surface.

[0017] S1.2. The fins 100 of the heat dissipation substrate are subjected to shallow roughening treatment using a low-pressure sandblasting device. The sandblasting medium is 180-320 mesh alumina sand or glass beads, the spraying pressure is 0.15-0.40 MPa, and the spraying time is 10-45 s.

[0018] Using a low-pressure sandblasting device to perform shallow roughening treatment on the fins 100 can improve the surface roughness and surface activity of the fins 100 without significantly damaging the thin-walled structure of the fins 100. This makes it easier for subsequent carbon nanotubes to spread on the surface of the fins 100 and form a more continuous heat-releasing layer. The fins 100 are typically thinner and longer than the base 200, and mainly function to diffuse and release heat to the surrounding environment. Therefore, their surface treatment must enhance the adhesion of subsequent deposited layers without creating excessively deep gaps or causing localized stress concentrations. Using 180-320 mesh alumina sand or glass beads, combined with lower blasting pressure and shorter blasting time, can create a shallow rough texture on the surface of the fins 100.

[0019] S1.3. The surface-roughened heat dissipation substrate is placed in an organic solvent for degreasing treatment at a temperature of 20–40°C for 3–15 minutes. The degreased substrate is then transferred to an ultrasonic cleaning device and cleaned with deionized water and a weakly alkaline cleaning solution at an ultrasonic frequency of 20–60 kHz, an ultrasonic power of 100–500 W, and a treatment time of 5–20 minutes. The substrate is then dried with clean nitrogen gas. The weakly alkaline cleaning solution includes at least one of sodium carbonate solution, sodium bicarbonate solution, sodium metasilicate solution, and trisodium phosphate solution. The organic solvent includes at least one of ethanol, isopropanol, and acetone. The pH of the weakly alkaline cleaning solution is 8.0–10.5. When the heat dissipation substrate contains copper, the weakly alkaline cleaning solution also includes a benzotriazole corrosion inhibitor.

[0020] The surface-roughened heat dissipation substrate is first degreased in an organic solvent, then transferred to an ultrasonic cleaning device for cleaning with deionized water and a weakly alkaline cleaning solution. This effectively removes oil, sandblasting residue particles, fine dust, and some loose deposits from the surface of the heat dissipation substrate, truly exposing the roughened surface and creating cleaner interface conditions for subsequent hydrophilic activation and carbon nanotube deposition. At least one of ethanol, isopropanol, and acetone is selected as the organic solvent. These solvents have good dissolving power for oil and organic residues. Ethanol and isopropanol have good volatility and are gentler, while acetone has a stronger ability to remove some stubborn organic matter. Subsequently, ultrasonic cleaning with deionized water and a weakly alkaline cleaning solution further dislodges and removes fine particles from the microgrooves, micropits, and surface gaps of the fins.

[0021] S1.4 Place the dried heat dissipation substrate in a wet activation device for hydrophilic activation treatment. The activation solution is a hydrogen peroxide solution with a concentration of 0.1-2 wt% or a citric acid / hydrogen peroxide mixture. The treatment temperature is 20-40℃ and the treatment time is 1-10 min.

[0022] The dried heat dissipation substrate is placed in a wet activation device and hydrophilically activated using a 0.1–2 wt% hydrogen peroxide solution or a citric acid / hydrogen peroxide mixture. This improves the surface energy and wetting ability of the heat dissipation substrate, making it easier for the subsequent carbon nanotube dispersion to spread on the surfaces of the base 200 and fins 100 and enter the roughened microstructure. Hydrogen peroxide has a certain oxidizing effect, which can remove some residual organic matter on the surface and promote the formation of a more stable hydrophilic oxide layer on the metal surface. When citric acid and hydrogen peroxide are mixed, citric acid can gently complex the metal surface, helping to clean some loose inorganic residues, while hydrogen peroxide continues to provide an oxidative activation effect. The combination of the two can improve the surface hydrophilicity without significantly damaging the substrate. After this step, the surface of the heat dissipation substrate changes from a state that is relatively difficult to wet to a state that is more easily wetted by the dispersion liquid. In this way, during the subsequent deposition process, the carbon nanotube dispersion liquid can more evenly cover the surface of the base 200 and the fin 100, reducing local shrinkage, blank areas and deposition breakage, which is conducive to the subsequent formation of a more continuous heat-conducting layer and an oriented heat-releasing layer.

[0023] S1.5. The heat dissipation substrate that has undergone hydrophilic activation treatment is subjected to vacuum drying treatment, with a vacuum degree of [missing information]. 0.04~ The heat dissipation preform was obtained by applying a pressure of 0.09 MPa, a processing temperature of 40–80 °C, and a processing time of 10–40 min.

[0024] Vacuum drying of the hydrophilically activated heat dissipation substrate removes residual moisture and volatile components from the surface and microstructure after activation, while stabilizing the activated surface state and preventing residual liquid from interfering with the subsequent carbon nanotube deposition process. The vacuum level is [missing information]. 0.04~ The conditions of 0.09 MPa, a processing temperature of 40–80 °C, and a processing time of 10–40 min are sufficient to remove residual moisture from the rough structure of the base 200 and the surface of the fins 100, without causing excessive changes in the metal surface state due to excessively high temperatures. If there is a lot of residual moisture on the surface, it may lead to unstable local electric field distribution during subsequent electric field deposition, and may also cause uneven dilution of the carbon nanotube dispersion when it comes into contact with the substrate surface, thus affecting the uniformity of deposition.

[0025] S2. Carbon nanotubes and dispersant are added to a dispersion medium to disperse them and obtain a carbon nanotube dispersion. The heat dissipation preform is placed in the carbon nanotube dispersion. The base 200 is used as a deposition electrode to apply an electric field consistent with the target heat conduction direction, so that the carbon nanotubes are deposited on the base 200 to form an oriented heat conduction layer. The direction of the electric field is adjusted so that the carbon nanotubes are deposited on the fins 100 to form an oriented heat release layer, thus obtaining a deposition composite.

[0026] Step S2 includes: S2.1 Prepare a first dispersion medium and a second dispersion medium. The first dispersion medium includes deionized water and a monohydric alcohol, and the second dispersion medium includes deionized water and a polyhydric alcohol. The monohydric alcohol includes at least one of ethanol, isopropanol, and n-propanol, with a deionized water:monohydric alcohol ratio of 6:4 to 9:1. The polyhydric alcohol includes at least one of ethylene glycol, propylene glycol, and glycerol, with a deionized water:monohydric alcohol ratio of 7:3 to 9:1.

[0027] By preparing a first dispersion medium and a second dispersion medium separately, different liquid-phase deposition environments can be provided for the base 200 and the fin 100, making the subsequently formed carbon nanotube layers more suitable for their respective functional requirements. The first dispersion medium consists of deionized water and monohydric alcohols. Among them, monohydric alcohols such as ethanol, isopropanol, and n-propanol evaporate quickly and have low viscosity, which can improve the dispersion state of carbon nanotubes in the liquid and enhance the migration ability of carbon nanotubes under the action of an electric field. Therefore, they are more suitable for forming a denser and more oriented thermally conductive layer in the base 200 region. The second dispersion medium consists of deionized water and polyhydric alcohols. Among them, ethylene glycol, propylene glycol, and glycerol have relatively higher viscosity and slower evaporation, which can make the liquid film maintain a more stable spreading state on the surface of the fin 100 and reduce local shrinkage and agglomeration during the deposition process. Therefore, it is more suitable for forming a more open and more uniform oriented heat-releasing layer in the fin 100 region. The main function of deionized water is to provide a stable liquid environment and reduce the impact of impurity ions on deposition behavior; monohydric alcohols and polyhydric alcohols respectively regulate evaporation rate, viscosity, and wettability. Through this step, the deposition conditions of the base 200 and fin 100 can be distinguished, laying the foundation for the subsequent differentiated construction of functional layers.

[0028] S2.2. Single-walled carbon nanotubes and ethyl acetate are mixed and dispersed to obtain a pre-dispersed slurry of single-walled carbon nanotubes. Then, the pre-dispersed slurry of single-walled carbon nanotubes and a dispersant are added to a first dispersion medium for dispersion to obtain a first carbon nanotube dispersion. The concentration of carbon nanotubes in the first carbon nanotube dispersion is 0.05-0.60 mg / mL, and the amount of dispersant added is 0.1%-1.0% of the mass of the first dispersion medium. The dispersion is first pre-dispersed at 1000-5000 r / min for 5-20 min, and then ultrasonically treated. The ultrasonic frequency is 20-40 kHz, the ultrasonic power is 200-800 W, and the ultrasonic time is 20-60 min. The temperature is controlled at 15-30℃ during the treatment. The dispersant includes at least one of sodium dodecylbenzenesulfonate, polyvinylpyrrolidone, and Tween 80. The diameter of the single-walled carbon nanotubes is 1-5 nm and the length is 1-8 μm.

[0029] Dispersing single-walled carbon nanotubes (SUVs) with a dispersant in a first dispersion medium yields a first SUV dispersion more suitable for deposition of the thermally conductive layer in the base 200. SUVs, with their smaller diameter and higher aspect ratio, are more likely to form continuous, fine thermally conductive pathways in an oriented state, making them more suitable for placement in areas like the base 200 requiring rapid heat conduction. By controlling the SUV concentration, dispersant dosage, and pre-dispersion and ultrasonic treatment conditions, entanglement and aggregation between SUVs can be reduced, maintaining a more uniform dispersion in the liquid. Sodium dodecylbenzenesulfonate, a surfactant, can coat the SUV surface with its hydrophilic and hydrophobic molecular structures, improving its dispersion stability in the liquid. Polyvinylpyrrolidone (PVP) creates steric hindrance on the SUV surface, reducing re-agglomeration. Tween 80 also improves the wetting effect of the liquid on the SUVs, helping to form a stable dispersion. High-speed pre-dispersion followed by ultrasonic treatment breaks down larger initial agglomerates and further separates smaller bundles. Controlling the processing temperature between 15 and 30°C can prevent carbon nanotubes from re-entangled or the dispersant's performance from deteriorating due to excessively high local temperatures during dispersion. This step improves the controllability of the deposition stage of the substrate 200, resulting in a more continuous and uniform heat-conducting layer.

[0030] S2.3. Multi-walled carbon nanotubes and a dispersant are added to a second dispersion medium for dispersion to obtain a second carbon nanotube dispersion. The concentration of carbon nanotubes in the second carbon nanotube dispersion is 0.02–0.30 mg / mL, and the amount of dispersant added is 0.05%–0.8% of the mass of the second dispersion medium. The mixture is first stirred at 300–800 r / min for 10–25 min, and then subjected to ultrasonic treatment. The ultrasonic frequency is 20–40 kHz, the ultrasonic power is 150–600 W, and the ultrasonic time is 10–40 min. The temperature is controlled at 20–35℃ during the treatment. The diameter of the multi-walled carbon nanotubes is 10–40 nm, and the length is 5–20 μm.

[0031] Dispersing multi-walled carbon nanotubes (MWCNTs) and a dispersant in a second dispersion medium yields a second CNT dispersion more suitable for the deposition of the heat-releasing layer on fin 100. Compared to single-walled CNTs, MWCNTs have larger diameters and more stable structures, making it easier to form an overlapping network with a certain skeletal support on the surface of fin 100. This network maintains heat diffusion capacity while also preserving surface openness, preventing the formation of an excessively dense covering layer. The lower concentration of carbon nanotubes and the relatively lower amount of dispersant in the second CNT dispersion help avoid the formation of an excessively thick deposition layer on the surface of fin 100, thus preserving the effective heat transfer area of ​​fin 100. Using low-speed stirring combined with ultrasonic treatment can ensure the dispersion of MWCNTs while reducing the impact of excessive shearing on their length and network formation ability. The polyol in the second dispersion medium helps maintain the stability of the liquid film on the surface of fin 100 and slows down the liquid evaporation rate, allowing MWCNTs more time to spread and overlap along the surface of fin 100. This step allows for a more uniform and open oriented heat release layer in the fin 100 area, which facilitates the diffusion and release of heat on the surface of the fin 100.

[0032] S2.4 Install the heat dissipation preform in the partitioned electric field deposition device, and electrically connect the base 200 to the conductive fixture so that the base 200 serves as the deposition electrode. Then place the heat dissipation preform in the first carbon nanotube dispersion and control the temperature of the deposition solution to 20-35°C.

[0033] The heat dissipation prefabricated component is installed in a zoned electric field deposition apparatus, and the base 200 is electrically connected to a conductive fixture, making the base 200 the deposition electrode. The heat dissipation prefabricated component is then placed in a first carbon nanotube dispersion. This allows the deposition process to initially concentrate in the base 200 area, rather than proceeding indiscriminately across the entire heat sink surface. The practical effect of this is to allow the base 200 to first form a stable thermally conductive layer foundation, preventing the fins 100 from competing with the base 200 for deposition in the early stages, which would lead to dispersed carbon nanotube distribution and insufficient local deposition. The zoned electric field deposition apparatus controls the energized area, the electrode position, and the deposition area, allowing the base 200 to preferentially receive a stronger and more stable electric field. Controlling the deposition solution temperature between 20 and 35°C helps maintain the viscosity, conductivity, and carbon nanotube dispersion state of the dispersion, reducing deposition unevenness caused by temperature fluctuations. This step makes the deposition process on the base 200 more concentrated and controllable, improving the integrity and continuity of the subsequent extraction of the thermally conductive layer.

[0034] S2.5. Apply an electric field to the base 200 in the same direction as the target heat conduction direction, so that the carbon nanotubes migrate directionally to the surface of the base 200 and are deposited on the base 200 to form an outward heat conduction layer. The applied voltage is 20-100V, the electrode spacing is 10-40mm, and the deposition time is 3-20min. During the deposition process, a circulating pump or microfluidic stirrer is used to circulate the first carbon nanotube dispersion at a low speed of 0.05-0.50m / s to form an outward heat conduction layer.

[0035] If the single-walled carbon nanotubes are modified with a magnetic component, such as iron(II,III) oxide or cobalt ferrite, an auxiliary magnetic field is applied simultaneously with the deposition of the substrate 200 using an electric field. The direction of the magnetic field is consistent with the target heat conduction direction, and the magnetic field strength is 0.05–0.50 T. The application time of the auxiliary magnetic field is the same as the deposition time of the substrate 200.

[0036] Applying an electric field aligned with the target heat conduction direction to the base 200 causes carbon nanotubes to migrate directionally to and deposit on the surface of the base 200, forming a heat-conducting layer extending along a predetermined direction on the surface of the base 200. Since single-walled carbon nanotubes themselves have high axial thermal conductivity, when they are arranged relatively uniformly along the heat transfer direction, heat can propagate through the base 200 region via shorter, more continuous paths, thereby reducing localized heat accumulation. Controlling the voltage, electrode spacing, and deposition time allows for the gradual formation of a more uniform coating layer of carbon nanotubes on the surface of the base 200, avoiding both insufficient deposition and layer instability caused by excessively thick local deposition. Using a circulating pump or microfluidic stirrer for low-speed circulation during deposition helps maintain a relatively uniform carbon nanotube concentration in the first carbon nanotube dispersion, reducing concentration gradients near the base 200 caused by localized consumption. Simultaneously applying an auxiliary magnetic field aligned with the target heat conduction direction further improves the uniformity of carbon nanotube arrangement along this direction, making the formed heat-conducting layer structurally more unidirectional in heat transfer. After this treatment, the heat-conducting layer on the surface of the base 200 not only adheres more evenly, but also facilitates the rapid conduction of heat from the heat source to the fin 100 area.

[0037] S2.6. Adjust the electrodes in the partitioned electric field deposition device to connect to the fins 100, and adjust the electric field direction to match at least one of the following: the length direction of the fins 100, the thermal diffusion direction of the fin surface 100, and the normal heat release direction of the fins 100. Transfer the fins 100 of the heat dissipation preform into the second carbon nanotube dispersion, apply an electric field to the fins 100, with an applied voltage of 10-60V, an electrode spacing of 10-35mm, and a deposition time of 2-15min to form an oriented heat release layer. If the single-walled carbon nanotubes are modified with a magnetic component, such as iron(III) oxide or cobalt ferrite, then an auxiliary magnetic field is applied during the deposition of the fins 100. The direction of the auxiliary magnetic field is consistent with the length direction of the fins 100 or forms a preset angle with the normal direction of the outer surface of the fins 100. The magnetic field strength is 0.03-0.25T, and the action time is 1-10min.

[0038] After the heat-guiding layer is deposited on the base 200, the electrodes in the partitioned electric field deposition device are connected to the fins 100, and the electric field direction is adjusted to match at least one of the following: the length direction of the fins 100, the heat diffusion direction on the surface of the fins 100, and the normal heat release direction of the fins 100. Then, the fins of the heat dissipation prefabrication are transferred into the second carbon nanotube dispersion, and an electric field is applied to the fins 100. This allows multi-walled carbon nanotubes to preferentially deposit on the surface of the fins 100 and form an oriented heat release layer. After this treatment, the carbon nanotubes on the fins 100 are no longer just randomly covered, but tend to form a more continuous heat diffusion network along the surface of the fins 100 or the length direction of the fins 100, which is beneficial for spreading the heat from the base 200 along the surface of the fins 100 as quickly as possible. Since the multi-walled carbon nanotubes in the second carbon nanotube dispersion are more likely to form spatial overlapping structures, a more open deposition layer can be formed on the surface of the fins 100 under lower voltage and shorter deposition time conditions, avoiding excessive clogging of the fin surface. Applying an auxiliary magnetic field during the deposition process further helps the multi-walled carbon nanotubes adjust their orientation along a predetermined direction, reducing surface entanglement and ensuring that the heat-releasing layer on the surface of the fin 100 maintains both thermal conductivity continuity and a good open surface structure. This step allows the fin 100 to more effectively perform surface heat expansion and external heat release functions, thereby improving the overall heat dissipation efficiency of the heat sink.

[0039] S2.7 Remove the heat dissipation preform from the second carbon nanotube dispersion and let it stand for 30s to 5min. Then, use clean nitrogen to blow away the attached liquid at a pressure of 0.01 to 0.08MPa to obtain the deposited composite.

[0040] After the heat dissipation preform is removed from the second carbon nanotube dispersion, it is allowed to stand. Then, clean nitrogen is used to remove the adhering liquid. This removes excess liquid from the surface and crevices without significantly damaging the formed deposition layer, reducing the risk of localized agglomeration, sagging, or uneven layer shrinkage caused by excessive liquid residue during subsequent drying and fixing processes. A standing period of 30 seconds to 5 minutes allows the liquid film adhering to the base 200 and fins 100 to initially redistribute, gradually transitioning the carbon nanotube network in the heat-conducting and oriented heat-releasing layers from a flowing state to a relatively stable state. Subsequently, clean nitrogen is used to gently remove unstable adhering liquid while minimizing recontamination of the deposition surface by external dust and moisture. Controlling the purging pressure between 0.01 and 0.08 MPa balances liquid removal effectiveness and deposition layer stability, preventing excessive purging from dispersing localized carbon nanotubes. This step ensures that the carbon nanotube layer already formed on the base 200 and fins 100 retains a relatively complete initial structure, providing conditions for subsequent fixing processes and ultimately obtaining a stable deposited composite.

[0041] S3. The deposited composite is dehydrated, the heat-conducting layer is hot-pressed and densified, the oriented heat-releasing layer is vacuum heat-fixed, and then an auxiliary fixing liquid is sprayed on. After drying, a heat sink containing carbon nanotubes is obtained.

[0042] Step S3 includes: S3.1. Perform rotary dehydration on the deposited composite at a rotation speed of 50–300 r / min for 10–120 s, while simultaneously performing air purging with nitrogen or clean air at a pressure of 0.01–0.08 MPa for 10–180 s.

[0043] Rotational dehydration of the deposited composite, combined with airflow purging, removes unstable liquid adhering to the surface and crevices of the deposited layer, mitigating localized agglomeration, bubbles, and uneven shrinkage caused by excessive residual liquid during subsequent drying and heat treatment. Rotational dehydration utilizes centrifugal force to dislodge free liquid from the deposited composite, reducing the liquid film thickness on the base 200 and fins 100. Airflow purging further removes any remaining liquid from the surface irregularities and gaps in the fins 100. Nitrogen or clean air is used as the purging gas to prevent recontamination of the deposited layer by dust, moisture, and impurities in ordinary air. Nitrogen is more stable and better at reducing the impact of the external environment on the deposited layer. This step allows the carbon nanotube layer on the surface of the deposited composite to reach a relatively stable state earlier, providing more uniform initial conditions for subsequent low-temperature drying and heat treatment, and reducing the possibility of structural disturbance by liquid during subsequent processing.

[0044] S3.2 Place the deposited composite material that has completed the liquid removal treatment in a hot air circulating oven for staged low-temperature drying treatment. The first stage drying temperature is 35-60℃ and the treatment time is 10-40 min; the second stage drying temperature is 55-90℃ and the treatment time is 10-50 min.

[0045] The deposited composite, after liquid removal, is placed in a hot air circulating oven for staged low-temperature drying. This process gently removes residual deionized water, monohydric alcohols, polyhydric alcohols, and trace amounts of volatile components carried by the dispersant from the deposited layer, minimizing the damage to the carbon nanotube alignment caused by rapid liquid evaporation. The first stage uses a lower temperature to allow residual liquid on the surface to evaporate slowly, reducing the phenomenon of localized agglomeration of carbon nanotubes caused by sudden liquid film contraction. The second stage, with increased temperature, further removes the more difficult-to-evaporate components within the deposited layer, gradually transitioning the thermally conductive and heat-releasing layers from a liquid-supported state to a more stable solid network state. Since compounds such as ethanol, isopropanol, n-propanol, ethylene glycol, propylene glycol, and glycerol are used in the dispersion medium, these compounds have different evaporation rates and viscosities. Without staged low-temperature drying, the drying rates of the base 200 and fin 100 surfaces could differ significantly, affecting the uniformity of subsequent layers. This step allows the deposited layer to achieve initial fixation under gentler conditions, reducing cracks, uneven shrinkage, and localized detachment of the deposited layer.

[0046] S3.3, The heat-conducting layer is densified by vacuum hot pressing, with a vacuum degree of [missing information]. 0.04~ The hot pressing pressure is 0.095 MPa, the hot pressing temperature is 80-180℃, the hot pressing pressure is 1-8 MPa, the holding time is 30s-20min, after the hot pressing is completed, it is placed in a constant temperature chamber for heat preservation at a temperature of 70-150℃ for 5-60min, and then cooled to room temperature at a rate of 1-10℃ / min.

[0047] The heat-conducting layer is densified by vacuum hot pressing, which further compacts the carbon nanotubes on the surface of the base 200 and makes them adhere more tightly to the roughened surface of the base 200, thereby improving the continuity and interfacial contact stability of the heat-conducting layer. Vacuum conditions facilitate the removal of residual gas and small amounts of volatiles from the heat-conducting layer, reducing the formation of local voids during hot pressing. Under certain temperature and pressure, the carbon nanotube bundles on the surface of the base 200 will move closer together, increasing the number of contact points and enhancing the mechanical interlocking between the carbon nanotubes and the micro-rough structure of the base 200. This facilitates heat transfer from the base 200 to the carbon nanotube layer. After hot pressing, the layer is kept at a constant temperature and then cooled to room temperature at a slow rate. This releases some of the thermal stress generated during the hot pressing process, reducing the likelihood of localized warping, cracking, or weakened adhesion of the heat-conducting layer during subsequent use. Through this step, the heat-conducting layer on the base 200 will change from a relatively loose structure formed by the initial deposition to a more stable and dense heat-conducting layer, which is more conducive to the base 200 undertaking the role of rapid heat dissipation.

[0048] S3.4. The oriented heat-releasing layer undergoes vacuum thermal consolidation treatment. The deposited composite is placed in a vacuum drying oven for heating treatment, with a vacuum degree of [missing information]. 0.05~ The pressure is 0.095 MPa, the heating rate is 1-8℃ / min, the treatment temperature is 90-180℃, the treatment time is 20-180 min, and after vacuum heat consolidation treatment, it is placed in a constant temperature chamber for heat preservation at a temperature of 80-160℃ for 10-120 min, the heating rate is 1-5℃ / min, and the cooling rate is 1-8℃ / min until it drops to room temperature.

[0049] Vacuum thermal consolidation of the oriented heat-releasing layer can improve its structural stability and adhesion reliability while minimizing disruption to the unfolded state of the carbon nanotube network on the fin 100 surface. Unlike the thermally conductive layer of the base 200, the heat-releasing layer on the fin 100 surface needs to maintain a certain degree of continuity while retaining more open surface space. This facilitates heat diffusion on the fin 100 surface and release into the outside air, making vacuum thermal consolidation more suitable than high-pressure densification. The low-pressure environment in the vacuum drying oven helps to remove residual volatiles and micro-gases from the heat-releasing layer, while the heating process helps to gradually stabilize the contact nodes in the carbon nanotube network. After vacuum thermal consolidation, the layer is placed in a constant-temperature chamber and treated at set heating and cooling rates. This allows the heat-releasing layer on the fin 100 surface to undergo further structural adjustments under a relatively stable thermal history, reducing subsequent localized loosening and peeling caused by uneven thermal expansion and contraction. Through this step, the oriented heat-releasing layer on the fin 100 can more easily maintain a good adhesion state while maintaining the open characteristics of the surface, thereby improving the stability of the fin 100 during the continuous heat release process.

[0050] S3.5. An auxiliary fixing liquid is sprayed onto the outer surfaces of the heat-conducting layer and the oriented heat-releasing layer of the deposited composite. The spraying pressure is 0.01–0.20 MPa, the spraying distance is 50–300 mm, and the spraying time is 5–120 s. Then, the surface is dried at a temperature of 40–90 °C for 5–60 min to obtain a heat sink containing carbon nanotubes. The auxiliary fixing liquid includes at least one of the following: a silicone resin solution with a concentration of 1 wt%–15 wt%, a silane coupling agent solution with a concentration of 0.1 wt%–8 wt%, a polyimide precursor solution with a concentration of 1 wt%–12 wt%, a phenolic resin diluent with a concentration of 1 wt%–10 wt%, an epoxy resin diluent with a concentration of 1 wt%–10 wt%, and an F2311 solution with a concentration of 1 wt%–12 wt%.

[0051] Spraying an auxiliary fixing liquid onto the outer surface of the conductive heat-conducting layer and the oriented heat-releasing layer of the deposited composite, followed by drying, further fixes the carbon nanotube network in its outer layer and the contact area with the substrate surface. This improves the overall adhesion of the carbon nanotube layer and reduces the risk of detachment during handling, assembly, or long-term thermal cycling. The auxiliary fixing liquid penetrates the surface of the carbon nanotube network after spraying and forms a thin fixing layer after drying. Among the components, silicone resin solution has good heat resistance, silane coupling agent solution helps improve the bonding between carbon nanotubes and the metal surface, polyimide precursor solution forms a relatively stable heat-resistant structure after drying, and phenolic resin and epoxy resin diluents provide some film-forming and fixing effects. Controlling the spraying pressure, spraying distance, and spraying time ensures that the auxiliary fixing liquid is mainly distributed on the surface and shallow areas of the conductive and heat-releasing layers, preventing excessive accumulation. A drying process at 40–90°C removes the solvent components from the auxiliary fixing liquid, leaving the fixing components on the surface and contact points of the carbon nanotube layer.

[0052] Please refer to Figure 1 , Figure 3 , Figure 4 as well as Figure 5 This invention proposes a heat sink containing carbon nanotubes, which is manufactured by the method described above. The heat sink containing carbon nanotubes includes a base 200, fins 100, a heat-conducting layer disposed on the base 200, and an oriented heat-releasing layer disposed on the fins 100. Both the heat-conducting layer and the oriented heat-releasing layer contain carbon nanotubes. The heat-conducting layer is used to construct a heat conduction path extending along the target heat conduction direction, and the oriented heat-releasing layer is used to construct a heat diffusion and heat release path extending along the surface of the fins 100.

[0053] The target heat conduction direction can be with Figure 1As shown in the figure, the direction in which the base 200 extends toward the fin 100 is consistent, or in other embodiments, the target heat conduction direction is along the plane of the base 200.

[0054] During use, the heat generated by the power device or chip is first transferred to the base 200. The heat-conducting layer on the base 200 constructs a relatively continuous heat conduction path along the target heat conduction direction, enabling heat to be directed more quickly from the local heat source area to the fin 100 area. After the heat enters the fin 100, the oriented heat-releasing layer on the surface of the fin 100 forms a diffusion network along the surface or length of the fin, allowing the heat to spread across multiple fin areas and be released outward through heat exchange between the fin surface and the air. This reduces the temperature peak at the heat source contact surface, increases the degree to which the far-end fins participate in heat dissipation, and reduces heat retention at the transition between the base and the fins.

[0055] Example 1: First, an integrally molded aluminum alloy heat sink is provided as the heat dissipation substrate. The heat dissipation substrate includes a base 200 and fins 100. The base 200 has dimensions of 80mm × 75mm × 8mm, the fins 100 have a height of 30mm, and there are 24 fins 100. The heat dissipation substrate undergoes surface pretreatment. A directional sandblasting device is used to roughen the surface of the base 200. The sandblasting medium is 120-mesh alumina sand, the spray pressure is controlled at 0.45MPa, the angle between the spray gun and the surface of the base 200 is controlled at 45°, the scanning speed is 60mm / s, and the processing time is 45s. Subsequently, a low-pressure sandblasting device is used to perform shallow roughening treatment on the fins 100. The sandblasting medium is 240-mesh glass beads, the spray pressure is 0.22MPa, and the spraying time is 20s. The heat dissipation substrate, after surface roughening treatment, was degreased in ethanol at 25°C for 8 minutes. The degreased substrate was then transferred to an ultrasonic cleaning device and cleaned with deionized water and sodium bicarbonate solution (0.8 wt% sodium bicarbonate solution concentration, deionized water to sodium bicarbonate solution volume ratio 4:1, ultrasonic frequency 40 kHz, ultrasonic power 250 W, treatment time 10 minutes). It was then dried with clean nitrogen. Next, the dried substrate was placed in a wet activation device for hydrophilic activation with a 1 wt% hydrogen peroxide solution at 25°C for 5 minutes. After hydrophilic activation, the substrate was vacuum dried at a vacuum degree of [missing information]. The heat dissipation preform was obtained by applying a pressure of 0.06 MPa, a processing temperature of 60℃, and a processing time of 20 min.

[0056] The carbon nanotube dispersion was then prepared. First, a first dispersion medium and a second dispersion medium were prepared. The first dispersion medium consisted of deionized water and ethanol, with a volume ratio of deionized water to ethanol of 8:2. The second dispersion medium consisted of deionized water and propylene glycol, with a volume ratio of deionized water to propylene glycol of 8:2. First, single-walled carbon nanotubes (SUVs) were mixed with ethyl acetate and then dispersed to obtain a pre-dispersed slurry of SUVs, wherein the pre-dispersed concentration of SUVs in ethyl acetate was 0.80 mg / mL. Then, the pre-dispersed slurry of SUVs was added to a first dispersion medium, followed by the addition of sodium dodecylbenzenesulfonate and polyvinylpyrrolidone at a mass ratio of 1:1, with a total addition amount of 0.40% of the mass of the first dispersion medium. The mixture was pre-dispersed at 2500 r / min for 10 min, and then subjected to ultrasonic treatment at a frequency of 30 kHz, an ultrasonic power of 400 W, and an ultrasonic time of 30 min, with the temperature controlled at 22℃ during the treatment, to obtain a first carbon nanotube dispersion, wherein the concentration of SUVs was 0.20 mg / mL. Step S2.3 is modified as follows: Multi-walled carbon nanotubes and Tween 80 are added to the second dispersion medium for dispersion. The amount of Tween 80 added is 0.20% of the mass of the second dispersion medium. The mixture is first stirred at 500 r / min for 15 min, and then subjected to ultrasonic treatment. The ultrasonic frequency is 30 kHz, the ultrasonic power is 250 W, and the ultrasonic time is 20 min. The temperature is controlled at 28 ℃ during the treatment to obtain the second carbon nanotube dispersion, wherein the concentration of multi-walled carbon nanotubes is 0.10 mg / mL.

[0057] The heat dissipation preform was installed in a partitioned electric field deposition apparatus, and the base 200 was electrically connected to a conductive fixture, making the base 200 the deposition electrode. The heat dissipation preform was then placed in a first carbon nanotube dispersion, and the deposition solution temperature was controlled at 25°C. An electric field aligned with the target heat conduction direction was applied to the base 200, with a voltage of 50V, an electrode spacing of 20mm, and a deposition time of 8 minutes. During the deposition process, a circulating pump was used to circulate the first carbon nanotube dispersion at a low speed of 0.15m / s, causing the single-walled carbon nanotubes to migrate directionally to the surface of the base 200 and deposit there, forming an outward heat-conducting layer. No auxiliary magnetic field was applied during this process. Subsequently, the electrodes in the partitioned electric field deposition apparatus were connected to the fin 100, and the electric field direction was adjusted to match the length direction of the fin 100. The fins of the heat dissipation preform were then transferred into the second carbon nanotube dispersion. An electric field of 25V was applied to the fin 100, the electrode spacing was 18mm, and the deposition time was 6min, allowing multi-walled carbon nanotubes to be deposited on the surface of the fin 100, forming an oriented heat-releasing layer. No auxiliary magnetic field was applied during the deposition process of the fin 100. After deposition, the heat dissipation preform was removed from the second carbon nanotube dispersion, allowed to stand for 2min, and then clean nitrogen gas was used to remove the adhering liquid at a pressure of 0.03MPa, resulting in the deposited composite.

[0058] Finally, the deposited composite was post-treated. First, the composite was subjected to rotary dehydration at 120 r / min for 40 s, simultaneously purged with nitrogen gas at 0.03 MPa for 40 s. Then, the dehydrated composite was placed in a hot air circulating oven for staged low-temperature drying. The first stage drying temperature was 45℃ for 20 min, and the second stage drying temperature was 70℃ for 25 min. Finally, the heat-conducting layer was densified by vacuum hot pressing at a vacuum level of [missing information]. The hot-pressing pressure was 3 MPa at 120℃ and 0.07 MPa for 5 minutes. After hot pressing, the composite was placed in a constant temperature chamber at 100℃ for 20 minutes, followed by cooling to room temperature at a rate of 3℃ / min. The oriented heat-releasing layer was then subjected to vacuum thermal consolidation. The deposited composite was placed in a vacuum drying oven for heating treatment at a vacuum degree of [missing information]. The heat was applied at 0.08 MPa, with a heating rate of 3℃ / min, a treatment temperature of 130℃, and a treatment time of 50 min. After vacuum heat consolidation, the material was placed in a constant temperature chamber for heat preservation at 110℃ for 30 min, with a heating rate of 2℃ / min and a cooling rate of 3℃ / min, until it reached room temperature. Finally, an auxiliary fixing liquid was sprayed onto the outer surface of the heat-conducting layer and the orientation heat-releasing layer of the deposited composite. The auxiliary fixing liquid was a 5wt% organosilicon resin solution. The spraying pressure was 0.05 MPa, the spraying distance was 120 mm, and the spraying time was 20 s. Then, it was dried at 60℃ for 20 min to obtain a heat sink containing carbon nanotubes prepared without the use of a magnetic field.

[0059] Example 2: In Example 2, the heat dissipation substrate is a copper-aluminum composite heat sink, with the base 200 having a copper layer and the fins 100 having an aluminum layer. In step S1, the sandblasting medium for the base 200 is changed to 150-mesh silicon carbide sand, the spraying pressure is 0.50 MPa, the scanning speed is 50 mm / s, and the processing time is 50 s; the shallow roughening of the fins 100 still uses 240-mesh glass beads, the spraying pressure is 0.25 MPa, and the spraying time is 25 s. The degreasing treatment used isopropanol at 30°C for 10 minutes. The weakly alkaline cleaning solution was replaced with a sodium metasilicate solution at 0.6 wt%, with a deionized water to sodium metasilicate solution volume ratio of 4:1. This weakly alkaline cleaning solution also included a benzotriazole corrosion inhibitor, specifically benzotriazole, added at 0.05 wt% of the total mass of the weakly alkaline cleaning solution. The ultrasonic frequency was 45 kHz, the ultrasonic power was 300 W, and the treatment time was 12 minutes. The hydrophilic activating solution was replaced with a citric acid / hydrogen peroxide mixture, with 0.5 wt% citric acid and 1 wt% hydrogen peroxide, treated at 30°C for 6 minutes. Vacuum drying conditions were as follows: 0.07MPa, 65℃, 25min.

[0060] In Example 2, the first dispersion medium consisted of deionized water and isopropanol in a volume ratio of 7:3; the second dispersion medium consisted of deionized water and glycerol in a volume ratio of 8.5:1.5. First, single-walled carbon nanotubes were mixed with ethyl acetate and then dispersed to obtain a pre-dispersed slurry of single-walled carbon nanotubes, wherein the pre-dispersed concentration of single-walled carbon nanotubes in ethyl acetate was 1.00 mg / mL. Then, the pre-dispersed slurry was added to the first dispersion medium, followed by sodium dodecylbenzenesulfonate and polyvinylpyrrolidone in a mass ratio of 2:1, with a total addition amount of 0.50% of the mass of the first dispersion medium. The mixture was pre-dispersed at 3000 r / min for 12 min, and then subjected to ultrasonic treatment at a frequency of 35 kHz, an ultrasonic power of 500 W, and an ultrasonic time of 35 min, with the temperature controlled at 20°C during the treatment, to obtain a first carbon nanotube dispersion with a single-walled carbon nanotube concentration of 0.30 mg / mL. Step S2.3 is modified as follows: Multi-walled carbon nanotubes and Tween 80 are added to the second dispersion medium for dispersion. The amount of Tween 80 added is 0.25% of the mass of the second dispersion medium. The mixture is first stirred at 600 r / min for 18 min, then subjected to ultrasonic treatment at a frequency of 30 kHz, a power of 300 W, and a duration of 25 min. The temperature is controlled at 26℃ during the treatment to obtain a second carbon nanotube dispersion with a multi-walled carbon nanotube concentration of 0.12 mg / mL. For deposition on the base 200, the deposition solution temperature is 24℃, the voltage is 60 V, the electrode spacing is 18 mm, the deposition time is 10 min, the circulation flow rate is 0.18 m / s, and the auxiliary magnetic field strength is 0.20 T. For deposition on the fins 100, the voltage is 30 V, the electrode spacing is 16 mm, the deposition time is 7 min, the auxiliary magnetic field strength is 0.10 T, and the reaction time is 6 min. The settling time is 2 min, and the nitrogen purging pressure is 0.04 MPa.

[0061] The post-processing conditions in Example 2 were also adjusted accordingly. The rotary dehydration speed was 150 r / min for 50 s, the nitrogen purging pressure was 0.04 MPa, and the purging time was 60 s. The first stage of low-temperature drying was 50°C for 25 min, and the second stage was 75°C for 30 min. The hot-pressing densification conditions for the 200mm thermally conductive layer of the base were as follows: The heat treatment conditions were 0.08 MPa, 130℃, 4 MPa, 6 min; the holding conditions were 110℃, 25 min; and the cooling rate was 3℃ / min. The vacuum thermal consolidation conditions for the finned 100 heat release layer were... The initial spraying conditions were 0.08 MPa, 140℃, and 60 min, followed by a heat preservation condition of 120℃ and 35 min. The auxiliary fixing liquid was changed to a mixture of 3 wt% silane coupling agent solution and 4 wt% polyimide precursor solution in a 1:1 mass ratio. The spraying pressure was 0.06 MPa, the spraying distance was 100 mm, the spraying time was 25 s, and the drying conditions were 70℃ and 25 min, resulting in a heat sink containing carbon nanotubes.

[0062] Example 3: In Example 3, a copper alloy heat sink is selected as the heat dissipation substrate, which includes a base 200 and fins 100. Step S1 is performed first. A directional sandblasting device is used to roughen the surface of the base 200. The sandblasting medium is 130-mesh alumina sand, the spraying pressure is 0.55 MPa, the angle between the spray gun and the surface of the base 200 is 40°, the scanning speed is 45 mm / s, and the processing time is 55 s. A low-pressure sandblasting device is used to perform shallow roughening of the fins 100. The sandblasting medium is 200-mesh alumina sand, the spraying pressure is 0.28 MPa, and the spraying time is 22 s. The heat dissipation substrate, after surface roughening treatment, was placed in a mixed solvent of acetone and ethanol for degreasing, with a volume ratio of acetone to ethanol of 1:1, a treatment temperature of 25°C, and an immersion time of 6 minutes. The degreased substrate was then transferred to an ultrasonic cleaning device, where it was cleaned with a mixture of deionized water, sodium carbonate solution, and sodium bicarbonate solution. The mass ratio of sodium carbonate solution to sodium bicarbonate solution was 1:1, with a total concentration of 0.9 wt%. The mixture also included a benzotriazole corrosion inhibitor, specifically methylbenzotriazole, added at 0.06 wt% of the total mixture mass. The ultrasonic frequency was 40 kHz, the ultrasonic power was 280 W, and the treatment time was 10 minutes. The substrate was then dried with clean nitrogen. After drying, the substrate was placed in a wet activation device for hydrophilic activation treatment. The activation solution was a 1.2 wt% hydrogen peroxide solution, the treatment temperature was 28°C, and the treatment time was 4 minutes. After hydrophilic activation, the heat dissipation substrate undergoes vacuum drying treatment at a vacuum degree of [missing information]. The heat dissipation preform was obtained by applying a pressure of 0.08 MPa, a processing temperature of 70°C, and a processing time of 20 min.

[0063] Then proceed to step S2. First, prepare the first dispersion medium and the second dispersion medium. The first dispersion medium is composed of deionized water and n-propanol, with a volume ratio of deionized water to n-propanol of 7.5:2.5. The second dispersion medium is composed of deionized water and ethylene glycol, with a volume ratio of deionized water to ethylene glycol of 8:2. First, single-walled carbon nanotubes (SUVs) were mixed with ethyl acetate and then dispersed to obtain a pre-dispersed slurry of SUVs, wherein the pre-dispersed concentration of SUVs in ethyl acetate was 1.20 mg / mL. Then, the pre-dispersed slurry was added to a first dispersion medium, followed by the addition of sodium dodecylbenzenesulfonate, polyvinylpyrrolidone, and Tween 80 in a mass ratio of 2:1:1, with a total addition amount of 0.60% of the mass of the first dispersion medium. The mixture was pre-dispersed at 3500 r / min for 15 min, and then subjected to ultrasonic treatment at a frequency of 35 kHz, an ultrasonic power of 550 W, and an ultrasonic time of 40 min, with the temperature controlled at 18 °C during the treatment, to obtain a first carbon nanotube dispersion, wherein the concentration of SUVs was 0.35 mg / mL. Step S2.3 is modified as follows: Multi-walled carbon nanotubes, polyvinylpyrrolidone, and Tween 80 are added to the second dispersion medium for dispersion. The mass ratio of polyvinylpyrrolidone to Tween 80 is 1:1, and the total amount added is 0.30% of the mass of the second dispersion medium. The mixture is first stirred at 650 r / min for 20 min, and then subjected to ultrasonic treatment. The ultrasonic frequency is 30 kHz, the ultrasonic power is 320 W, and the ultrasonic time is 25 min. The temperature is controlled at 25 ℃ during the treatment to obtain the second carbon nanotube dispersion, in which the concentration of multi-walled carbon nanotubes is 0.15 mg / mL.

[0064] The heat dissipation preform was installed in a partitioned electric field deposition apparatus, and the base 200 was electrically connected to a conductive fixture, making the base 200 the deposition electrode. The heat dissipation preform was then placed in a first carbon nanotube dispersion, and the deposition solution temperature was controlled at 24°C. An electric field aligned with the target heat conduction direction was applied to the base 200, with a voltage of 70V, an electrode spacing of 15mm, and a deposition time of 12min. During deposition, a circulating pump was used to circulate the first carbon nanotube dispersion at a low speed of 0.20m / s. Simultaneously, an auxiliary magnetic field was applied, aligned with the target heat conduction direction, with a magnetic field strength of 0.25T. The auxiliary magnetic field was applied for the same duration as the deposition time of the base 200, causing the single-walled carbon nanotubes to migrate directionally to the surface of the base 200 and deposit there, forming an outward heat-conducting layer.

[0065] Subsequently, the electrodes in the partitioned electric field deposition device were connected to the fin 100, and the direction of the electric field was adjusted to match the length direction of the fin 100. The fins of the heat dissipation preform were then transferred into the second carbon nanotube dispersion. An electric field was applied to the fin 100 with a voltage of 35V, an electrode spacing of 15mm, and a deposition time of 8min, so that multi-walled carbon nanotubes were deposited on the surface of the fin 100 to form an oriented heat-releasing layer. During the deposition process of the fin 100, an auxiliary magnetic field was applied with the direction of the auxiliary magnetic field consistent with the length direction of the fin 100, a magnetic field strength of 0.12T, and an application time of 6min.

[0066] Between steps S2.6 and S2.7, the process further includes: S2.6a, after the oriented heat-releasing layer is formed on the fin 100, Tween 80 and polyvinylpyrrolidone are added to the second carbon nanotube dispersion, wherein the mass ratio of Tween 80 to polyvinylpyrrolidone is 1:1, and the total amount added is 0.05% of the mass of the second dispersion medium. Then, the heat dissipation preform is rotated 180° around the central axis of the base 200, while maintaining the fin 100 connected to the adjusted electrode. A secondary short-time electric field deposition treatment is performed in the second carbon nanotube dispersion, with an applied voltage of 15V and a deposition time of 2 minutes, so that the sidewalls and top of the fin 100 form a connected reinforcing heat-releasing network. The preform is then removed and allowed to stand. After completing the above steps, the heat dissipation preform is removed from the second carbon nanotube dispersion, allowed to stand for 3 minutes, and then clean nitrogen is used to remove the adhering liquid at a purging pressure of 0.04 MPa, resulting in a deposited composite.

[0067] Finally, step S3 is performed. First, the deposited composite is subjected to rotary dehydration at a speed of 180 r / min for 60 s, while simultaneously purging with nitrogen gas at a pressure of 0.05 MPa for 60 s. Then, the dehydrated composite is placed in a hot air circulating oven for staged low-temperature drying. The first stage drying temperature is 55℃ for 25 min, and the second stage drying temperature is 80℃ for 35 min. Finally, the heat-conducting layer is densified by vacuum hot pressing at a vacuum degree of [missing information]. The hot-pressing pressure was 5 MPa at 140℃ and 0.085 MPa, with a holding time of 8 min. After hot pressing, the composite was placed in a constant temperature chamber at 120℃ for 30 min, followed by cooling to room temperature at a rate of 2℃ / min. The oriented heat-releasing layer was then subjected to vacuum thermal consolidation. The deposited composite was placed in a vacuum drying oven for heating treatment at a vacuum degree of [missing information]. The heat was applied at 0.09 MPa, with a heating rate of 3℃ / min, a treatment temperature of 150℃, and a treatment time of 70 min. After vacuum heat consolidation, the material was placed in a constant temperature chamber for heat preservation at 125℃ for 40 min, with a heating rate of 2℃ / min and a cooling rate of 3℃ / min until it reached room temperature. Finally, an auxiliary fixing liquid was sprayed onto the outer surface of the heat-conducting layer and the orientation heat-releasing layer of the deposited composite. The auxiliary fixing liquid was a mixture of 6 wt% silicone resin solution and 3 wt% silane coupling agent solution in a mass ratio of 2:1. The spraying pressure was 0.05 MPa, the spraying distance was 110 mm, and the spraying time was 25 s. The material was then dried at 75℃ for 30 min to obtain a heat sink containing carbon nanotubes.

[0068] Comparative Example 1: Comparative Example 1 is based on Example 1, and all other parts not described are the same as in Example 1. The difference is that Comparative Example 1 does not perform electric field operation, auxiliary magnetic field operation, or spray auxiliary fixation liquid during the carbon nanotube deposition process.

[0069] Specifically, after obtaining the heat dissipation preform in step S1, the first carbon nanotube dispersion and the second carbon nanotube dispersion are prepared according to the method in Example 1. The first dispersion medium consists of deionized water and ethanol, with a deionized water:ethanol ratio of 8:2; the second dispersion medium consists of deionized water and propylene glycol, with a deionized water:propylene glycol ratio of 8:2. The concentration of single-walled carbon nanotubes in the first carbon nanotube dispersion is 0.20 mg / mL, and the dispersant is sodium dodecylbenzenesulfonate and polyvinylpyrrolidone in a mass ratio of 1:1, with a total addition amount of 0.40% of the mass of the first dispersion medium. The concentration of multi-walled carbon nanotubes in the second carbon nanotube dispersion is 0.10 mg / mL, and the dispersant is Tween 80, with an addition amount of 0.20% of the mass of the second dispersion medium.

[0070] In the deposition step, the heat dissipation preform was first immersed in the first carbon nanotube dispersion for 3 minutes, then removed and allowed to stand for 1 minute. It was then immersed in the second carbon nanotube dispersion for 3 minutes, removed, and allowed to stand for 2 minutes. No electric field or auxiliary magnetic field was applied throughout the process. Subsequently, clean nitrogen gas at 0.03 MPa was used to purge away the adhering liquid, resulting in the deposited composite. Then, following the S3 step of Example 1, the sample was subjected to rotary dehydration, staged low-temperature drying, hot-pressing densification of the base 200, and vacuum thermal consolidation of the fins 100 to obtain the Comparative Example 1 sample.

[0071] Comparative Example 2: Comparative Example 2 is also set up based on Example 1. The rest of the undescribed parts are the same as those in Example 1. The difference is that in the deposition process, Comparative Example 2 only performs overall electric field operation, does not distinguish between the base 200 and the fin 100, and does not spray auxiliary fixing liquid.

[0072] Specifically, after obtaining the heat dissipation preform in step S1, a first carbon nanotube dispersion and a second carbon nanotube dispersion are still prepared separately. However, during actual deposition, the base 200 and the fin 100 are not processed separately. Instead, the first and second carbon nanotube dispersions are mixed at a volume ratio of 1:1 to obtain a mixed carbon nanotube dispersion. In this mixed carbon nanotube dispersion, the final concentration of single-walled carbon nanotubes is 0.10 mg / mL, the final concentration of multi-walled carbon nanotubes is 0.05 mg / mL, and the total addition amount of sodium dodecylbenzenesulfonate, polyvinylpyrrolidone, and Tween 80 is 0.30% of the mass of the mixed dispersion medium.

[0073] The heat dissipation preform was integrally mounted in an electric field deposition apparatus, placing the entire preform as a deposition object in a mixed carbon nanotube dispersion, and depositing it as a whole under a uniform electric field. The voltage was set to 40V, the electrode spacing to 20mm, the deposition time to 10min, and the deposition solution temperature to 25℃. During deposition, a circulating pump was used for low-speed circulation at a flow rate of 0.15m / s. Throughout the process, no switching of electrode connection areas was performed, and the base 200 and fin 100 were not distinguished, nor was the electric field direction of fin 100 adjusted individually. The sample was then removed, allowed to stand for 2min, and purged with clean nitrogen at 0.03MPa to remove adhering liquid, resulting in the deposited composite, which is the sample for Comparative Example 2.

[0074] The testing process for the improvement rate of in-plane equivalent thermal conductivity was as follows: Carbon nanotube-containing heat sink samples prepared in Examples 1, 2, 3, Comparative Example 1, and Comparative Example 2 were used as reference samples, along with blank heat sinks of the same size, material, and structure but without carbon nanotube composite treatment. First, test samples with dimensions of 20mm × 20mm × original thickness were cut from the 200°C area of ​​the base of each heat sink. After wiping the surface with anhydrous ethanol, the samples were placed in an environment of 25°C and 50% relative humidity for 12 hours to eliminate the influence of residual surface moisture on the test results. Then, a laser thermal conductivity meter was used to test the samples at a temperature of 25°C. Each sample was tested three times consecutively, and the average value was taken as the thermal diffusivity result. Next, the sample density was determined using the Archimedes displacement method, the specific heat capacity was determined using differential scanning calorimetry, and the in-plane equivalent thermal conductivity of each sample was calculated using the thermal conductivity calculation formula. Finally, using the in-plane equivalent thermal conductivity of the blank heat sink as a benchmark, the improvement rate of the in-plane equivalent thermal conductivity is calculated according to "(in-plane equivalent thermal conductivity of the test sample - in-plane equivalent thermal conductivity of the blank heat sink) / in-plane equivalent thermal conductivity of the blank heat sink × 100%".

[0075] The test procedure for the 35W steady-state temperature drop was as follows: Heat sinks prepared in each embodiment and comparative example were installed on electric heating modules of the same specifications. The effective heating surface size of the electric heating module was 30mm × 30mm, and the input power was constantly set to 35W. Thermal grease of the same thickness was uniformly applied between the heat sink base 200 and the electric heating module, controlling the grease thickness to approximately 0.10mm. The modules were then fixed with screws of the same torque to ensure consistent installation contact conditions for each group of samples. The test environment was a natural air convection environment, with an ambient temperature controlled at 25±1℃, relative humidity controlled at 50%±5%, and an ambient wind speed less than 0.2m / s. During heating, a K-type thermocouple was used to measure the temperature near the heat source contact surface, and an infrared thermal imager was used to assist in monitoring the surface temperature distribution of the heat sink. The temperature acquisition interval was 10s. Steady-state was considered reached when continuous heating for 60 minutes or when the temperature change rate was less than 0.2℃ / min. Record the temperature of the heat source contact surface when each sample reaches steady state, and compare it with the steady-state temperature of the blank heat sink under the same conditions. The difference between the two is the 35W steady-state temperature drop. Each group of samples was tested in parallel three times, and the average value was taken as the final result.

[0076] The process for testing the layer retention rate after 200 thermal cycles was as follows: Samples prepared in each embodiment and comparative example were placed in a thermal cycling test chamber and cycled between 25°C and 125°C. Each cycle included: heating from 25°C to 125°C for 15 minutes; holding at 125°C for 15 minutes; cooling to 25°C for 15 minutes; and finally holding at 25°C for 15 minutes, constituting one complete cycle. A total of 200 thermal cycles were performed. After the thermal cycles, the samples were removed and placed at room temperature for 2 hours. The layer retention was then evaluated using a combination of optical microscopy and weighing. Specifically, the initial mass or initial coverage area of ​​the carbon nanotube layer before thermal cycling was recorded, and the residual mass or residual coverage area after thermal cycling was measured. The layer retention rate was calculated as "residual value after thermal cycling / initial value × 100%". Three samples were tested in each group, and the average value was taken as the final result. This experiment mainly reflects the adhesion stability and structural retention ability of carbon nanotube layers under repeated thermal expansion and contraction conditions.

[0077] The experimental data obtained from the above experimental process are shown in Table 1.

[0078] Table 1: The data on the improvement rate of in-plane equivalent thermal conductivity show that Examples 1, 2, and 3 reached 31%, 36%, and 42%, respectively, significantly higher than the 14% of Comparative Example 1 and the 22% of Comparative Example 2. This indicates that after adopting partitioned deposition, constructing a heat-conducting layer oriented at the base 200, and constructing a heat-releasing layer oriented at the fins 100, the heat transfer pathways inside and on the surface of the heat sink are more continuous, and the heat diffusion ability in the heat sink is significantly enhanced. In particular, Example 3 showed the highest improvement rate, indicating that by further optimizing the deposition conditions and adding a heat-releasing network reinforced by the fins 100 in Example 3, carbon nanotubes formed a more effective heat-conducting and heat-diffusing structure on the surfaces of the base 200 and the fins 100, which can more fully utilize the high axial thermal conductivity of the carbon nanotubes themselves.

[0079] Based on the steady-state temperature drop data at 35W, Examples 1, 2, and 3 achieved 9.8℃, 11.4℃, and 13.2℃ respectively, all significantly better than Comparative Example 1's 4.2℃ and Comparative Example 2's 6.8℃. This result indicates that, under the same heating conditions, the example samples can more effectively dissipate the heat input from the heat source from the base 200 and further release it to the surrounding environment through the fins 100, thus resulting in a more significant temperature drop at the heat source contact surface. Example 3 exhibits the largest steady-state temperature drop, indicating the best synergistic effect between its base 200 heat-conducting layer and fin 100 heat-releasing layer. In particular, the formation of a connected reinforcing network between the sidewalls and top of the fins 100 further enhances the heat diffusion and heat release capabilities of the three-dimensional surface of the fins 100, resulting in better overall heat dissipation.

[0080] The layer retention rates after 200 thermal cycles were 93%, 95%, and 97% for Examples 1, 2, and 3, respectively, significantly higher than 76% for Comparative Example 1 and 84% for Comparative Example 2. This indicates that the carbon nanotube layers in the example samples remained relatively stable on the surface of the heat dissipation substrate after repeated heating and cooling, and were not prone to significant detachment, cracking, or localized peeling. Among them, Example 3 had the highest layer retention rate, indicating that under the multiple treatments of hot pressing densification of the base 200, vacuum thermal consolidation of the fins 100, and auxiliary fixing liquid spraying, the stability between the carbon nanotube layer and the substrate, as well as within the carbon nanotube layer, was better, resulting in superior thermal cycling resistance.

[0081] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, and improvements made within the spirit and principles of the present invention should be included within the protection scope of the present invention.

Claims

1. A method for preparing a heat sink containing carbon nanotubes, characterized in that the steps include... include: S1. The heat dissipation substrate is subjected to surface roughening treatment, degreasing cleaning and hydrophilic activation treatment to obtain heat dissipation preform, wherein the heat dissipation substrate includes a base and fins. S2. Carbon nanotubes and dispersant are added to a dispersion medium to disperse carbon nanotubes to obtain a carbon nanotube dispersion. The heat dissipation preform is placed in the carbon nanotube dispersion. The base is used as a deposition electrode to apply an electric field consistent with the target heat conduction direction, so that carbon nanotubes are deposited on the base to form an oriented heat conduction layer. The direction of the electric field is adjusted to deposit carbon nanotubes on the fins to form an oriented heat release layer, thus obtaining a deposition composite. S3. The deposited composite is dehydrated, the heat-conducting layer is hot-pressed and densified, the oriented heat-releasing layer is vacuum heat-fixed, and then an auxiliary fixing liquid is sprayed on. After drying, a heat sink containing carbon nanotubes is obtained.

2. The method for preparing a heat sink containing carbon nanotubes according to claim 1, characterized in that, Step S1 includes: S1.

1. The base of the heat dissipation substrate is roughened by a directional sandblasting device. The sandblasting medium is 100-180 mesh alumina sand or silicon carbide sand, the spraying pressure is 0.35-0.65MPa, the angle between the spray gun and the base surface is controlled at 30-60°, the scanning speed is 30-120mm / s, and the processing time is 20-90s. S1.

2. A low-pressure sandblasting device is used to perform shallow roughening treatment on the fins of the heat dissipation substrate. The sandblasting medium is 180-320 mesh alumina sand or glass beads, the spraying pressure is 0.15-0.40 MPa, and the spraying time is 10-45 s. S1.

3. The heat dissipation substrate after surface roughening treatment is placed in an organic solvent for degreasing treatment. The treatment temperature is 20-40℃ and the soaking time is 3-15min. The degreased heat dissipation substrate is transferred to an ultrasonic cleaning device and cleaned with deionized water and weak alkaline cleaning solution. The ultrasonic frequency is 20-60kHz, the ultrasonic power is 100-500W, and the treatment time is 5-20min. The substrate is then dried with clean nitrogen. S1.4 Place the dried heat dissipation substrate in a wet activation device for hydrophilic activation treatment. The activation solution is a hydrogen peroxide solution with a concentration of 0.1-2 wt% or a citric acid / hydrogen peroxide mixture. The treatment temperature is 20-40℃ and the treatment time is 1-10 min. S1.

5. The heat dissipation substrate that has undergone hydrophilic activation treatment is subjected to vacuum drying treatment, with a vacuum degree of [missing information]. 0.04~ The heat dissipation preform was obtained by applying a pressure of 0.09 MPa, a processing temperature of 40–80 °C, and a processing time of 10–40 min.

3. The method for preparing a heat sink containing carbon nanotubes according to claim 2, characterized in that, In step S1, the heat dissipation substrate includes one of aluminum alloy heat sink, copper alloy heat sink, and copper-aluminum composite heat sink. The weakly alkaline cleaning solution includes at least one of sodium carbonate solution, sodium bicarbonate solution, sodium metasilicate solution, and trisodium phosphate solution. The pH of the weakly alkaline cleaning solution is 8.0 to 10.

5. When the heat dissipation substrate contains copper, the weakly alkaline cleaning solution also includes a benzotriazole corrosion inhibitor. The organic solvent includes at least one of ethanol, isopropanol, and acetone.

4. The method for preparing a heat sink containing carbon nanotubes according to claim 1, characterized in that, Step S2 includes: S2.

1. Prepare a first dispersion medium and a second dispersion medium. The first dispersion medium includes deionized water and a monohydric alcohol, and the second dispersion medium includes deionized water and a polyhydric alcohol. S2.

2. Single-walled carbon nanotubes and ethyl acetate are mixed and dispersed to obtain a pre-dispersed slurry of single-walled carbon nanotubes. Then, the pre-dispersed slurry of single-walled carbon nanotubes and a dispersant are added to a first dispersion medium to obtain a first carbon nanotube dispersion. The concentration of single-walled carbon nanotubes in the first carbon nanotube dispersion is 0.05-0.60 mg / mL, and the amount of dispersant added is 0.1%-1.0% of the mass of the first dispersion medium. The dispersion is first pre-dispersed at 1000-5000 r / min for 5-20 min, and then ultrasonically treated. The ultrasonic frequency is 20-40 kHz, the ultrasonic power is 200-800 W, and the ultrasonic time is 20-60 min. The temperature is controlled at 15-30℃ during the treatment. S2.

3. Multi-walled carbon nanotubes and a dispersant are added to a second dispersion medium and dispersed to obtain a second carbon nanotube dispersion. The concentration of multi-walled carbon nanotubes in the second carbon nanotube dispersion is 0.02-0.30 mg / mL, and the amount of dispersant added is 0.05%-0.8% of the mass of the second dispersion medium. The mixture is stirred at 300-800 r / min for 10-25 min, and then subjected to ultrasonic treatment. The ultrasonic frequency is 20-40 kHz, the ultrasonic power is 150-600 W, and the ultrasonic time is 10-40 min. The temperature is controlled at 20-35℃ during the treatment. S2.4 Install the heat dissipation preform in the partitioned electric field deposition device, and electrically connect the base to the conductive clamp so that the base serves as the deposition electrode. Then place the heat dissipation preform in the first carbon nanotube dispersion and control the temperature of the deposition solution to 20-35°C. S2.5 Apply an electric field to the base in the same direction as the target heat conduction to cause carbon nanotubes to migrate directionally to the base surface and deposit on the base to form an outward heat conduction layer. The applied voltage is 20-100V, the electrode spacing is 10-40mm, and the deposition time is 3-20min. During the deposition process, a circulating pump or microfluidic stirrer is used to circulate the first carbon nanotube dispersion at a low speed of 0.05-0.50m / s to form an outward heat conduction layer. S2.

6. Adjust the electrodes in the partitioned electric field deposition device to connect to the fins, and adjust the electric field direction to match at least one of the fin length direction, fin surface heat diffusion direction, and fin normal heat release direction. Transfer the fins of the heat dissipation preform into the second carbon nanotube dispersion, apply an electric field to the fins, with an applied voltage of 10-60V, an electrode spacing of 10-35mm, and a deposition time of 2-15min to form an oriented heat release layer. S2.7 Remove the heat dissipation preform from the second carbon nanotube dispersion and let it stand for 30s to 5min. Then, use clean nitrogen to blow away the attached liquid at a pressure of 0.01 to 0.08MPa to obtain the deposited composite.

5. The method for preparing a heat sink containing carbon nanotubes according to claim 4, characterized in that, In step S2, the single-walled carbon nanotubes have a diameter of 1–5 nm and a length of 1–8 μm, the multi-walled carbon nanotubes have a diameter of 10–40 nm and a length of 5–20 μm, the monohydric alcohol includes at least one of ethanol, isopropanol, and n-propanol, the ratio of deionized water to monohydric alcohol is 6:4 to 9:1, the polyhydric alcohol includes at least one of ethylene glycol, propylene glycol, and glycerol, the ratio of deionized water to monohydric alcohol is 7:3 to 9:1, and the dispersant includes at least one of sodium dodecylbenzenesulfonate, polyvinylpyrrolidone, and Tween 80.

6. The method for preparing a heat sink containing carbon nanotubes according to claim 4, characterized in that, If the single-walled carbon nanotubes are modified with a magnetic component, such as iron(III) oxide or cobalt ferrite, then between steps S2.5 and S2.6, the following step is also included: An auxiliary magnetic field is applied simultaneously with the deposition of an electric field on the base. The direction of the magnetic field is consistent with the heat conduction direction of the target, and the magnetic field strength is 0.05-0.50T. The application time of the auxiliary magnetic field is the same as the deposition time of the base.

7. A method for preparing a heat sink containing carbon nanotubes according to claim 4 or 6, characterized in that, If the multi-walled carbon nanotubes are modified with a magnetic component, such as iron(III) oxide or cobalt ferrite, then between steps S2.6 and S2.7, An auxiliary magnetic field is applied during the fin deposition process. The direction of the auxiliary magnetic field is consistent with the length direction of the fin or forms a preset angle with the normal of the outer surface of the fin. The magnetic field strength is 0.03 to 0.25 T, and the application time is 1 to 10 min.

8. The method for preparing a heat sink containing carbon nanotubes according to claim 1, characterized in that, Step S3 includes: S3.

1. The deposited composite is subjected to rotary dehydration at a rotation speed of 50-300 r / min for 10-120 s, while air purging is performed simultaneously. The gas is nitrogen or clean air, the purging pressure is 0.01-0.08 MPa, and the purging time is 10-180 s. S3.2 Place the deposited composite material that has completed the liquid removal treatment in a hot air circulating oven for staged low-temperature drying treatment. The first stage drying temperature is 35-60℃ and the treatment time is 10-40 min; the second stage drying temperature is 55-90℃ and the treatment time is 10-50 min. S3.3, The heat-conducting layer is densified by vacuum hot pressing, with a vacuum degree of [missing information]. 0.04~ 0.095MPa, hot pressing temperature is 80~180℃, hot pressing pressure is 1~8MPa, holding time is 30s~20min, after hot pressing, it is placed in a constant temperature box for holding at 70~150℃ for 5~60min, and then cooled to room temperature at a rate of 1~10℃ / min. S3.

4. The oriented heat-releasing layer undergoes vacuum thermal consolidation treatment. The deposited composite is placed in a vacuum drying oven for heating treatment, with a vacuum degree of [missing information]. 0.05~ The pressure is 0.095 MPa, the heating rate is 1-8℃ / min, the treatment temperature is 90-180℃, the treatment time is 20-180 min, and after vacuum heat consolidation treatment, it is placed in a constant temperature chamber for heat preservation at a temperature of 80-160℃ for 10-120 min, with a heating rate of 1-5℃ / min and a cooling rate of 1-8℃ / min until it reaches room temperature. S3.

5. Spray an auxiliary fixing liquid onto the outer surface of the heat-conducting layer and the oriented heat-releasing layer of the deposited composite. The spraying pressure is 0.01-0.20 MPa, the spraying distance is 50-300 mm, and the spraying time is 5-120 s. Then dry it at a temperature of 40-90℃ for 5-60 min to obtain a heat sink containing carbon nanotubes.

9. The method for preparing a heat sink containing carbon nanotubes according to claim 8, characterized in that, In step S3, the auxiliary fixing liquid includes at least one of the following: a silicone resin solution with a concentration of 1 wt% to 15 wt%, a silane coupling agent solution with a concentration of 0.1 wt% to 8 wt%, a polyimide precursor solution with a concentration of 1 wt% to 12 wt%, a phenolic resin diluent with a concentration of 1 wt% to 10 wt%, an epoxy resin diluent with a concentration of 1 wt% to 10 wt%, and an F2311 solution with a concentration of 1 wt% to 12 wt%.

10. A heat sink containing carbon nanotubes, characterized in that, The heat sink containing carbon nanotubes is manufactured by a method for preparing a heat sink containing carbon nanotubes as described in any one of claims 1-9. The heat sink containing carbon nanotubes includes a base, fins, a heat-conducting layer disposed on the base, and an oriented heat-releasing layer disposed on the fins. Both the heat-conducting layer and the oriented heat-releasing layer contain carbon nanotubes. The heat-conducting layer is used to construct a heat conduction path extending along the target heat conduction direction, and the oriented heat-releasing layer is used to construct a heat diffusion and heat release path extending along the surface of the fins.